1989
DOI: 10.1007/bf02438936
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural organization of the isolated cortex in eggs ofNassarius reticulatus (Mollusca)

Abstract: We have studied the organization of the cortex in fertilized eggs ofNassarius reticulatus by examining rotary-shadowed whole mounts of isolated cortices in the transmission electron microscope. The following components were distinguished: (a) the plasma membrane, with clathrin-coated areas and coated pits, (b) microfilaments and microtubules, and (c) a tubulovesicular network of endoplasmic reticulum. Microfilaments were identified by labeling with heavy meromyosin, and microtubules with a monoclonal anti-tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Our previous study on the ultrastructural organization of the Nassarius egg cortex has demonstrated the presence of a network o f actin filaments (Speksnijder et al 1989). Conventional fluores;zence microscopy o f whole eggs stained with NBD-phallacidin, which is k n o w n to specifically label F-actin (Barak et al 1980), confirms this earlier study (Fig.…”
Section: Effects Of Con a On The Cortical Actin Networksupporting
confidence: 65%
See 2 more Smart Citations
“…Our previous study on the ultrastructural organization of the Nassarius egg cortex has demonstrated the presence of a network o f actin filaments (Speksnijder et al 1989). Conventional fluores;zence microscopy o f whole eggs stained with NBD-phallacidin, which is k n o w n to specifically label F-actin (Barak et al 1980), confirms this earlier study (Fig.…”
Section: Effects Of Con a On The Cortical Actin Networksupporting
confidence: 65%
“…In addition, washing off the bound Con A with eMG before polar lobe formation completely prevents the occurrence of Con A effects, whereas removal of bound Con A is no longer effective in completely preventing the effects of Con A once the eggs start forming a polar lobe. The increased ability of Con A binding sites to cross-link at the time of polar lobe formation coincides with an increased lateral mobility of plasma membrane lipids in the vegetal membrane (Speksnijder et al 1985a), as well as with a disappearance of microtubules from the egg cortex (Speksnijder et al 1989). These findings suggest that, before lobe formation (i.e.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most work has concentrated on ER in the peripheral layer of the egg, the cortex. The cortical ER forms a two-dimensional network parallel to the plasma membrane with connections to the internal ER network (Campanella and Andreucetti, 1977;Sardet, 1984;Luttmer and Longo, 1985;Sardet and Chang, 1987;Henson et al, 1989;Speksnijder et al, 1989a;Houliston and Elinson, 1991). In sea urchin and ascidian eggs, this cortical ER is capable of calcium uptake and release and contains a high-capacity, low-affinity calciumbinding protein as well as a high concentration of calcium (Oberdorf et al, 1986;Payan et al, 1986;Oberdorf et al,animal hemisphere, and to the decreased velocity of the calcium wave at fertilization in the vegetal hemisphere (Kline and Nuccitelli, 1985;Busa and Nuccitelli, 1985).…”
mentioning
confidence: 99%
“…In Nassarius, however, a detailed study of isolated cortices (Fig. 18) has not revealed any dramatic differences in the organization of the cortical cytoskeleton between the vegetal pole and other areas (Speksnijder et al, 1989).…”
Section: Morphogenetic Plasmsmentioning
confidence: 99%